Pengaruh Harga terhadap Keputusan Pembelian Produk Luxcrime - Nadya Tasya Rawi; Sarah Rouli Tambunan; Desri Wiana; Dewi Comala Sari; Edi Putra Berutu (Journal of Management and Creative Business, 2024)
Luxcrime is a local cosmetic brand produced by PT Luxury Cantika Indonesia. Its flagship product is Luxcrime Two Way Cake which is a combination of powder and foundation rolled into one. Luxcrime Two Way Cake has achieved the highest sales, surpassing international brands. One of the factors that influence purchasing decisions is the price which is below one hundred thousand rupiah. This study aims to determine the effect of price on purchasing decisions for Luxcrime products among students in Medan city. The type of research used is quantitative research. The data collection technique used in this study was the questionnaire method and used a Likert scale. The research sample consisted of 100 respondents, namely students in Medan city who knew Luxcrime Two Way Cake products, had bought Luxcrime Two Way Cake, and had watched Luxcrime Two Way Cake reviews on Tasya Farasya's social media accounts. The sampling method used was accidental sampling. Data analysis was carried out by simple regression and hypothesis testing using the SPSS 23 program. The results of simple regression calculations explain that the independent variable price has a positive effect on the dependent variable of purchasing decisions. Then based on the results of hypothesis testing, it is proven that H1 is accepted.